2009
DOI: 10.3382/japr.2009-00023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bedding material on footpad dermatitis in broiler chickens

Abstract: Bedding availability issues are arising rapidly in the broiler industry that may alter the type and quality of bedding available to growers to rear broiler chickens. Because birds are in direct contact with the litter, the potential impact of bedding materials on footpad health is of concern. In 3 successive trials, 8 different bedding sources (pine shavings, pine bark, chipped pine, mortar sand, ground hardwood pallets, chopped straw, ground door filler, and cotton-gin trash) were compared in side-by-side exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
123
4
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(155 citation statements)
references
References 17 publications
11
123
4
17
Order By: Relevance
“…Managing litter moisture is challenging in reused litter, especially during the last weeks of the growout. The important factors that influence moisture in the rearing environment include short downtimes between flocks, partial-house brooding, evaporative cooling systems, and poor drinking water management (Bilgili et al, 2009). Health issues and the incidence of breast burns and blisters, leg abnormalities, and footpad lesions are reported in the literature as partially due to poor litter conditions (Benabdewelil & Ayach, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Managing litter moisture is challenging in reused litter, especially during the last weeks of the growout. The important factors that influence moisture in the rearing environment include short downtimes between flocks, partial-house brooding, evaporative cooling systems, and poor drinking water management (Bilgili et al, 2009). Health issues and the incidence of breast burns and blisters, leg abnormalities, and footpad lesions are reported in the literature as partially due to poor litter conditions (Benabdewelil & Ayach, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The sustainability of broiler production requires bedding material to be environmentally friendly, and the replacement of litter needs to be efficient and cost-effective in order to be implemented by growers in a profitable way (Mayne et al, 2007;Bilgili et al, 2009). This requires the availability of alternative bedding sources, as well as good understanding of how to reduce NH 3 emissions in reused litter.…”
Section: Introductionmentioning
confidence: 99%
“…Substrates with sharp edges or chips may increase the prevalence and the severity of pododermatitis as a direct result of their abrasive action on the footpad. The function of the litter is to protect broilers' feet, minimizing the impact of the contact of the footpad with the floor (Bilgili et al, 2009). According to Refatti et al (2009), woodshavings litter caused a higher incidence of footpad lesions than sawdust.…”
Section: Resultsmentioning
confidence: 99%
“…Dawkins et al (2004) found that the presence of ammonia and moist litter deteriorate broiler health. The capacity of moisture absorption is one of the important features when choosing a litter substrate (Bilgili et al, 2009).…”
Section: Incidence Of Pododermatitis In Broiler Reared Under Two Typementioning
confidence: 99%
See 1 more Smart Citation